ANALISA KETERTARIKAN MINAT MAHASISWA TERHADAP TARIAN KHAS BETAWI LENGGANG NYAI DI UKM TRADITIONAL DANCE SEKOLAH TINGGI PARIWISATA TRISAKTI - Vienna Artina; Wijayanti Dewi Prabandari; Amelia Nur Annisa (Fakultas Pariwisata Universitas Pancasila, 2020)
Abstract Lenggang Nyai Dance is one of the new dance creations created by Wiwiek Widyastuti in 2002. The idea of ​​creating Lenggang Nyai Dance is a folklore of Nyai Dasimah. Lenggang Nyai dance has 2 values ​​which are positive values ​​for connoisseurs of art, consisting of moral values ​​and aesthetic values. The research method is descriptive correlation with Likert scale. The sampling technique used is with nonprobability sampling and with saturated sampling method. The research subjects were all members of the Traditional Dance Student Activity Unit who had danced the typical Betawi Lenggang Nyai dance, as many as 35 people. The results showed that dance uniqueness and interest have a strong enough relationship. Dance uniqueness also influences interest influenced by other factors. Simple linear regression test results from this study indicate that the uniqueness of the Lenggang Nyai dance causes a positive change towards student interest.